The Master of Library Science graduates of the Institute of Library Science, University of the Philippines, AY 1981-1992 a follow-up study - Robles, Ma. Narea Santiago 1967-
are now holding professional library positions. This supports the second proposition of this study that there is a significant relationship between the possession of an MLS degree and the graduates' access to career opportunities. As to the extent with which the MLS program has prepared the graduates for their present job, more than half (65 or 52.85) of the respondents answered they were prepared "extremely well."